Photodynamic Therapy in the Treatment of Persistent Central Serous Chorioretinopathy: a Two-Year Follow-Up - Valmaggia, C.; Haueter, I.; Niederberger, H. (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: The aim of this study was to assess during a follow-up period of two years the efficacy and safety of photodynamic therapy (PDT) in central serous chorioretinopathy (CSC) showing no spontaneous resolution four months after the onset of the symptoms. Patients and Methods: We present a prospective interventional non-comparative case series. The diagnosis of CSC was confirmed by fluorescein angiography (FA), and optical coherence tomography (OCT) in 46 eyes of 42 consecutive patients. PDT was performed according to the protocol used for treating choroidal neovascularization in age-related macular degeneration. The primary end point was to assess the anatomic re-attachment of the retina. The secondary end point was to record the visual function. A paired t-test and a linear regression and correlation test were used for the statistics. Results: The leakage in FA and the detachment of the neurosensory retina in OCT were no longer present in 42 eyes six weeks after PDT and in the remaining four eyes three months after PDT. At the end of the follow-up, the best-corrected visual acuity measured with an ETDRS chart improved in 36 eyes, and remained stable in 10 eyes (mean improvement, 10.2 letters; p < 0.001). Two cases of recurrence were diagnosed. No treatment-related complications were noticed. Conclusions: PDT could be an effective and durable option for treating patients with persistent CSC.
Keywords: photodynamic therapy; central serous chorioretinopathy